Information organization and production planning improvement in a clothes company in Portugal - Araújo, A. (2016)
In this paper we followed a qualitative research methodology through a case study, incorporating interviews with institutional actors involved (university, industry and government) in the cooperation project. Although this study is limited to a case study, however, highlight the importance of Triple Helix networks in order to develop the research presents a proposal for improvement for the first methodology of medium-sized textile company to address the modelling conceptual planning, production and control. In order to develop the research, development and innovation with the use of study methods which are: Planning and Production Control (PPC), master Production Planning (MPS), Materials Requirement Planning (MRP) Material, Capacity Planning using Global Factors (CPOF), and Capacity Requirement Planning (CRP). Through the practical perspective of a case study of Triple Helix successful cooperation, we were able to develop the cases considered to be studied on the organization and the production of information for structuring an improvement of data necessary to implement the methods of planning and selected information within the company.